Interaction between Marine-Derived n-3 Long Chain Polyunsaturated Fatty Acids and Uric Acid on Glucose Metabolism and Risk of Type 2 Diabetes Mellitus: A Case-Control Study - Kelei Li (Marine Drugs, 2015)
The present case-control study explored the interaction between marine-derived n-3 long chain polyunsaturated fatty acids (n-3 LC PUFAs) and uric acid (UA) on glucose metabolism and risk of type 2 diabetes mellitus (T2DM). Two hundred and eleven healthy subjects in control group and 268 T2DM subjects in case group were included. Plasma phospholipid (PL) fatty acids and biochemical parameters were detected by standard methods. Plasma PL C22:6n-3 was significantly lower in case group than in control group, and was negatively correlated with fasting glucose (r = −0.177, p < 0.001). Higher plasma PL C22:6n-3 was associated with lower risk of T2DM, and the OR was 0.32 (95% confidence interval (CI), 0.12 to 0.80; p = 0.016) for per unit increase of C22:6n-3. UA was significantly lower in case group than in control group. UA was positively correlated with fasting glucose in healthy subjects, but this correlation became negative in T2DM subjects. A significant interaction was observed between C22:6n-3 and UA on fasting glucose (p for interaction = 0.005): the lowering effect of C22:6n-3 was only significant in subjects with a lower level of UA. In conclusion, C22:6n-3 interacts with UA to modulate glucose metabolism.